2020
DOI: 10.4236/ajps.2020.113024
|View full text |Cite
|
Sign up to set email alerts
|

<i>Bredemeyera floribunda</i> Wild Elemental Content and Comparison with Nutritional Recommendation for Adults: Medicinal Plant Used by the Brazilian Rural Population to Treat Fatigue and Exhaustion

Abstract: Bredemeyera floribunda Wild (Polygalaceae), also known as pau-de-ovo is a medicinal plant used to treat snakebites, as tonic and fortifiers to treat fatigue and exhaustion. The aim of the present study was to document the knowledge of herbal sellers in the preparation of the so-called "B. floribunda fortifier" and to compare the plant root content with the recommended nutritional values and the permitted limit for medicinal plants. The study revealed that, unlike other regions of Brazil, in the Midwest region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 54 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…According to Judith [ 9 ], the crystals present in these plants are calcium oxaloacetate, which is found in greater quantities in the bark than in the root wood. In this way, our results showed that it was possible to obtain the extract and aerated cream, mimicking the popular tradition used to treat chronic fatigue, excessive tiredness, and low libido, as described by Tschinkel et al [ 17 ].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…According to Judith [ 9 ], the crystals present in these plants are calcium oxaloacetate, which is found in greater quantities in the bark than in the root wood. In this way, our results showed that it was possible to obtain the extract and aerated cream, mimicking the popular tradition used to treat chronic fatigue, excessive tiredness, and low libido, as described by Tschinkel et al [ 17 ].…”
Section: Discussionmentioning
confidence: 53%
“…Parts of this plant can be prepared in the form of decoction, infusion, maceration, and as juice, having applications in the treatment of diseases such as high blood pressure, liver, lung, and cardiovascular diseases [ 12 14 ], insect bites, snakes, and gynecological diseases [ 15 , 16 ]. In addition, in popular medicine, the bark of the root of B. floribunda is used against fatigue and exhaustion, increasing work activity and libido [ 17 ]. The root bark, when scraped and mixed with water, produces an aerated cream with a firm texture, which is ingested daily in the first meal of the day in rural areas [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations